2022
DOI: 10.5397/cise.2021.00353
|View full text |Cite
|
Sign up to set email alerts
|

Can platelet-rich plasma injections provide better pain relief and functional outcomes in persons with common shoulder diseases: a meta-analysis of randomized controlled trials

Abstract: Background: To evaluate the efficacy of autologous platelet-rich plasma (PRP) injections in the treatment of common shoulder diseases.Methods: The PubMed, Medline, and Central databases and trial registries were searched from their inception to July 2020 for randomized controlled trials of autologous PRP injections for shoulder diseases versus placebo or any control intervention. Preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines were followed in the selection, analysis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A study focusing on tendinopathy cases found that both PRP and corticosteroid injections led to improvements in patient symptoms. The study concluded that PRP could serve as a safe and effective alternative to corticosteroids, even over extended periods, to lessen both local and systemic effects associated with corticosteroid injections [32,33]. This treatment strategy could be especially advantageous for patients with diabetes, as PRP injections have been shown to be well-tolerated and safe [34].…”
Section: Lateral Elbow Painmentioning
confidence: 99%
“…A study focusing on tendinopathy cases found that both PRP and corticosteroid injections led to improvements in patient symptoms. The study concluded that PRP could serve as a safe and effective alternative to corticosteroids, even over extended periods, to lessen both local and systemic effects associated with corticosteroid injections [32,33]. This treatment strategy could be especially advantageous for patients with diabetes, as PRP injections have been shown to be well-tolerated and safe [34].…”
Section: Lateral Elbow Painmentioning
confidence: 99%
“…Therefore, integrating pharmacological interventions such as nonsteroidal anti-inflammatory drugs (NSAIDs) and analgesics becomes essential [132][133][134]. Additionally, personalized treatment plans, overseen by medical specialists, may incorporate intra-articular therapies like steroids, platelet-rich plasma (PRP), and hyaluronates to augment symptom management [135][136][137].…”
Section: Treatmentmentioning
confidence: 99%
“…If epicondylitis remains unimproved after 3 to 6 months of treatment, it is considered refractory and surgical intervention may be indicated. Conservative treatment encompasses exercise therapy, physical therapy, drug therapy, bracing, extracorporeal shock wave therapy, percutaneous pie crusting of the tendon origin [9] polydeoxyribonucleotide injections [10], platelet-rich plasma (PRP) injections [11], autologous blood injections [12], and local corticosteroid injection therapy.…”
Section: )Medialepicondylitismentioning
confidence: 99%